COLD BEAM INJECTION IN RELATIVISTIC EMEC WAVE FOR KAPPA DISTRIBUTION FUNCTION WITH AC FIELD FOR MAGNETO-PLASMA - Kaur, Rajbir; Pandey, R.S.; Singh, K.M.; Singh, B.N.; Prasad, Vijay (JOURNAL OF ADVANCES IN PHYSICS, 2015)
The effect of cold electron beam on electromagnetic electron cyclotron (EMEC) wave has been studied by using the unperturbed Lorentzian (Kappa) distribution in the magnetosphere for relativistic plasma. The dispersion relation is obtained by using the method of characteristic solutions and kinetic approach. An expression for the growth rate of a system has been calculated. It is inferred that in addition to the relativistic plasma obliquity and effect of cold electron beam modifies the growth rate and it also shifts the wave band significantly. The relativistic electrons by increasing the growth rate and widening the bandwidth may explain a wide frequency range of EMEC wave emissions in the magnetosphere.